Tailoring the refractive index of Ge-S based glass for 3D embedded waveguides operating in the mid-IR region - Bérubé, Jean-Philippe; Messaddeq, Sandra-Helena; Bernier, Michelle; Skripachev, Igor; Messaddeq, Younes [UNESP]; Vallée, Rene (Optica Publishing Group, 2014)
The photosensitivity of GeSx binary glasses in response to irradiation to femtosecond pulses at 800 nm is investigated. Samples with three different molecular compositions were irradiated under different exposure conditions. The material response to laser exposure was characterized by both refractometry and micro-Raman spectroscopy. It is shown that the relative content of sulfur in the glass matrix influences the photo-induced refractive index modification. At low sulfur content, both positive and negative index changes can be obtained while at high sulfur content, only a positive index change can be reached. These changes were correlated with variations in the Raman response of exposed glass which were interpreted in terms of structural modifications of the glass network. Under optimized exposure conditions, waveguides with positive index changes of up to 7.8x10−3 and a controllable diameter from 14 to 25 μm can be obtained. Direct inscription of low insertion losses (IL = 3.1 – 3.9 dB) waveguides is demonstrated in a sample characterized by a S/Ge ratio of 4. The current results open a pathway towards the use of Ge-S binary glasses for the fabrication of integrated mid-infrared photonic components.